1996
DOI: 10.1111/j.1440-6055.1996.tb01415.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of Trichogramma australicurn Girault (Hymenoptera: Trichogrammatidae) on Helicoverpa armigera (Hubner) Eggs (Lepidoptera: Noctuidae)

Abstract: Trichograrnma australicum were reared on eggs of Helicoverpa arrnigera. Immature T. australicurn were studied with a confocal laser scanning microscope and a light microscope. Development of egg, larva, prepupa and pupa required about 24-26, 24-26, 42-47 and 84-92 h, respectively, at 2 8 T , 45% RH and 12L:12D photoperiod. The eggs of T. australicurn increased significantly in size during incubation. The larval mandibles were gradually revealed as the larva increased in size. Exuviae were not found during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
4

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 13 publications
(35 reference statements)
0
22
0
4
Order By: Relevance
“…Teraoka & Numata, 1995;Howard & Baker, 2003). However, it was recorded that ecdysed Trichogramma adults may spend at least more than several hours within the host chorion (Dahlan & Gordh, 1996). Moreover, in gregarious Trichogramma species, males ecdyse earlier than females but do not emerge from the chorion and thus mating occurs inside the empty host egg (Lee et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Teraoka & Numata, 1995;Howard & Baker, 2003). However, it was recorded that ecdysed Trichogramma adults may spend at least more than several hours within the host chorion (Dahlan & Gordh, 1996). Moreover, in gregarious Trichogramma species, males ecdyse earlier than females but do not emerge from the chorion and thus mating occurs inside the empty host egg (Lee et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…data). The number of T. australicum females produced for every male in diet B is higher than the ratio of females to males produced in H. armigera eggs which is 1 S : 3 99 (Dahlan and Gordh 1996).…”
Section: Resultsmentioning
confidence: 98%
“…Most eggs of Trichogrammatidae are hymenopteriform in shape (Voegelé et al 1974, Pak and Oatman 1982, Dahlan and Gordh 1996, Jarjees and Merritt 2002, although stalked eggs are found in the genus Poropoea Förster (Clausen 1940). At oviposition, the eggs of the genus Trichogramma have a length of 100-140 μm and a width of 30-50 μm (Tanaka 1985a, Manweiler 1986, Saakian-Baranova 1990, Dahlan and Gordh 1996, Jarjees and Merritt 2002, but smaller eggs are laid by T. chilonis females (75 μm × 23 μm) (Tanaka 1985a). The eggs of Trichogrammatidae are hydropic (Jarjees and Merritt 2002) and they increase in size soon after oviposition as they absorb nutrient directly from the host through the egg membranes.…”
Section: Eggsmentioning
confidence: 99%
“…(Saakian-Baranova 1990, T. pintoi (Saakian-Baranova 1990), T. semblidis (Aurivillius) (Saakian-Baranova 1990), T. minutum (Manweiler 1986), T. platneri Nagarkatti (Saakian-Baranova 1990), T. brassicae Bezdenko (Wu et al 2000), T. maidis (Hawlitzky and Boulay 1982) and four in T. brevicapillum Pinto and Platner (Pak and Oatman 1982). Trichogramma australicum Girault, T. brassicae and T. cacoeciae were reported to have three larval instars (Brenière 1965, Saakian-Baranova 1990, but later studies reported only one instar (Volkoff et al 1995, Dahlan and Gordh 1996, 1997, Jarjees et al 1998, Wu et al 2000, Jarjees and Merritt 2002. Recent studies suggest that only one larval instar is present in Trichogramma based on the fact that the shape and size of the first (and only) larval instar change considerably during larval development because of important ingestion of food early in its development (see later).…”
Section: Number Of Instarsmentioning
confidence: 99%
See 1 more Smart Citation